Profile of the glaucomas and intervention in a large eye care centre in South-East Nepal - Sarkar, S; Mardin, C; Henning, A (Nepalese Journal of Ophthalmology, 2010)
Introduction: Glaucoma is the second leading cause of blindness worldwide. Objective:To estimate the prevalence and risk factors of glaucoma and modes of therapeutical intervention in a rural population of a developing country. Patients and methods: A single centre-based cross-sectional study was carried out over a seven-month period in Sagarmatha Choudhary Eye Hospital (SCEH), Lahan/NEPAL, including the patients with glaucoma. Outcome measurement: The patients' demography, type of the glaucomas, visual acuity, vertical cup-disc ratio, intra-ocular pressure and visual field findings were the parameters studied. Results: A total of 3986 eyes with suspected glaucoma were identified. 53.7 % of the patients were between 41- 60 years of age. 53.9 % were male. 26.5 % were blind or severely visually impaired. 37.2 % had IOP more than 35 mmHg. 46.4 % had vertical cup-disc ratio (VCDR) higher than 0.8. Severe visual field defects were found in 28.4 % eyes. 35.3% eyes had primary angle-closure glaucoma, 22.6 % eyes primary open-angle glaucoma, and 14.6 % eyes normaltension glaucoma. 10.2 % eyes suffered from lens induced glaucoma. Only in 9 eyes was pseudoexfoliation syndrome with glaucoma diagnosed. 25.7 % eyes were advised for trabeculectomy. 11.5 % eyes underwent extra-capsular cataract surgery. IOP lowering medication was prescribed in 5.9 % patients. Conclusions: The most common glaucoma seen in the out-patient department of a large eyecare centre in South-East Nepal is primary angle-closure glaucoma. 25 % of the glaucoma patients are visually impaired or blind at the time of presentation. In more than one-fourth of the patients, trabeculectomy is the therapy of choice. Keywords: glaucoma; South-East Nepal; North-East India; Bihar; blindness. DOI: 10.3126/nepjoph.v2i1.3697 Nep J Oph 2010;2(1):3-9